The Relationship Of Arabic and Malay Language In The Syair Gulung Ketapang West Kalimantan - Ardiansyah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aims to reveal the relationship between the two languages ​​in Syair Gulung. The form of the relation in this study is the emergence of absorbed words with various forms and phonological changes in Syair Gulung. This research used qualitative descriptive approach with library research and three stages: (1) Data collection, using Simak Bebas Cakap method and completed with Catat technique. (2) Data analysis using Padan Intralingual method completed with Hubung-Banding Menyamakan Hal Pokok technique. (3) Formal and informal presentation of the data analysis. This research concludes that the uptake words in Syair Gulong have a relationship between Arabic and Malay in the form of word uptake, solid uptake, and translation uptake. However, this relation cannot be separated from the absorbed words that undergo phonological changes.